The long-run effects of sports club vouchers for primary school children - Jan Marcus; Thomas Siedler; Nicolas R. Ziebarth (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Starting in 2009, the German state of Saxony distributed sports club membership vouchers among all 33,000 third graders in the state. The policy's objective was to encourage them to develop a long-term habit of exercising. In 2018, we carried out a large register-based survey among several cohorts in Saxony and two neighboring states. Our difference-indifferences estimations show that, even after a decade, awareness of the voucher program was significantly higher in the treatment group. We also find that youth received and redeemed the vouchers. However, we do not find significant short- or long-term effects on sports club membership, physical activity, overweightness, or motor skills.
Keywords: I12; I14; I18; I28; I38; Z28; H71; 330; physical activity; voucher; primary school; obesity; habit formation; objective health measures; school health examinations; windfall gains; crowding out; taxpayer subsidies